Impact of directional asymmetry on competition performance in judo: A pilot study - Simenko, J. (1st scientific and professional conference on judo "Applicable research in judo" - Book of abstracts, 2015)
Directional asymmetry is characterized by a symmetry distribution that is not centered around zero but is biased signi.cantly (Tomkins & Kotiaho, 2002) and is largely attributable to differential mechanical loading during bone growth, for example, handedness (Özener, 2010). Determining body (a)symmetries is important, because possible asymmetries may lead to severe physical consequences making it easier for the occurrence of injuries (Stradijot, Pittorru, & Pinna, 2012). DA has not been widely used in judo in connection to competitive performance, therefore the aim of this study is to present the relationship of DA to competitive performance in judokas.